ISLAMIC PERSPECTIVE ON TOURISM AND ITS BENEFITS - Firdaus Firdaus; Desmadi Saharuddin; Ilda Hayati (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Tourism has enormous benefits in Islam and even has a positive impact on One's faith. Tourism is a part of